RUSSIAN FEDERALISM AND RELIGION - Kuchenin, Evgeny; Lavrentieva, Maria; Turkin, Mikhail (Revista Inclusiones, 2020)
The modern Russian state has proclaimed freedom of conscience and religion as a constitutionally guaranteed human and civil right. The constitutional principle of freedom of conscience and religion is the result of a long process of the historical development of Russia, in which the economic, social and political circumstances and conditions that accompanied its existence were crucial. The importance of the constitutional and legal provision of religious rights and freedoms is necessary, first of all, for the free development of each person and the formation of a full-fledged civil society, as a necessary condition for building a legal and social state. The Russian Federation is a secular state, in which no religion can be established as a state or compulsory one. The formation of a secular state in Russia is associated with the constant expansion confessional space, search for a national ideology, lack of a clear state-confessional policy, which raises a number of practical challenges and problems. The coordination of the public interests of the state and society, religious associations and religious citizens, as well as citizens who do not profess any religion, is of paramount importance in matters of legal regulation in the sphere of religion.